METHODOLOGICAL RECOMMENDATIONS FOR IMPROVING THE LINGUISTIC FOUNDATIONS OF SAVANOV TEACHING TO STUDENTS WITH PROBLEMS IN MENTAL DEVELOPMEN - Abdujabborova Majvuda Bakhtiyor kizi (Bright Mind Publishing, 2025)
In Uzbekistan, disability is defined based on a combination of medical and charitable models: "a disabled person is a person who is in need of social assistance and protection due to his/her limited ability to work due to physical or mental disabilities." Raising the younger generation as healthy, strong, mentally and physically mature people is an important task in Uzbekistan. Thanks to independence, more attention is being paid to physical education and sports. This article discusses the linguistic foundations of teaching literacy to students with mental disabilities.
Keywords: Development, children, mental disability, linguistic, literacy, teaching, basis, social protection.